Strengthening trust or fuelling fears?: evaluation of a serious game on climate change adaptation - Wankmüller, Franziska; Siegmund, Alexander (International journal of disaster risk reduction, 2025)
To successfully adapt to climate change, existing knowledge gaps must be filled. An exemplary educational tool addressing climate change adaptation (CCA) is the serious game Klim:S21. The game shows future climate-related risks and protective effects of CCA measures. The game is designed for use in educational contexts and is being examined as part of a 90-min-long workshop concept. The workshop included an introduction to the game, guided tasks during gameplay, and a concluding reflection session. This study explores how the workshop concept affects objective and subjective knowledge about CCA. A further focus lies on its influence on participants’ trust in CCA measures and its potential to exacerbate climate-related fears. 707 pupils from German secondary schools (from 8th grade) took part in the intervention study. Participants were assigned to either a test group (cleaned N = 328) or a non-treatment control group (cleaned N = 92). Both groups completed the pre-test 2-3 weeks before taking part in the workshop, the control group filled in the post-test before the intervention took place. We examined knowledge in CCA and aspects of threat and coping appraisals. Our results showed a strong increase in knowledge about CCA in the test group. Aspects of coping increased significantly, while threat appraisals remained unchanged. No corresponding change was observed in the control group. We conclude that Klim:S21 can educate young people about CCA in a solution-oriented way without further fuelling fears of climate change.